(3efXheI aj GdYbGFO eY TQMgGs - (3GdbWjaj, Ydj Hf CMeO Hf GdMSjf Bd YHO GdLHGQ, J (B1287(3g`s
(3ChdgG (B:s
(3GdMeO ddg HeG UObJ eG(B***(3Ydeg GdUGOb ef JYdeGs
(3BNQgG (B:s
(3Cfg GdMb aj HYV ebGe GdQShd Udi Gddg Ydjg hSde hCgd HjJg, hdcf de jMUd dj aQGZ hGddg GdejSQ hGdYGde HGdUhGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B4(3, U(B260s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3GdJhMjO hGdedd hGdfMds